CONSTRUCTION OF CHARACTER BASED ON PANCASILA VALUES FOR STUDENTS - Warlim, Warlim (International Journal Pedagogy of Social Studies, 2023)
The fading of national character can be seen from the large number of people consuming drugs, the consumerist lifestyle, the practice of religious life which is only limited to formalism and symbols. The character crisis has now spread to the campus environment so that it is easy to find student attitudes and behavior that are contrary to moral values. As citizens who uphold the existence and harmony of national identity, the urgency of Pancasila values as the foundation of moral values in the life of society, nation and state needs to be implemented. Pancasila as the basis of the state and national ideology contains divine values, human values, unity values, social values and justice values. If humans are able to realize and really be able to carry out the five basic values contained in Pancasila, then the Indonesian nation can minimize the various conflicts that occur. Thus strengthening character through Pancasila values can unite the diversity of the Indonesian nation. Keywords: Character, Pancasila Values, Students